Impact of fuelwood quality and quantity on the energy use of rural households in the Omusati Region, north-central Namibia. Issue 4 (1st October 2016) - Hainduwa, Feliciana N; Ham, Cori; Meincken, Martina
Abstract : The relation between fuelwood use and fuelwood quality and quantity was studied in two northern Namibian rural communities with different levels of fuelwood availability. Household surveys were conducted and fuelwood quality was assessed through laboratory studies. The study found differences in fuelwood use and adaptation of liveli-hoods to fuelwood availability. Where there was an abundance of quality fuelwood, the community chose fuelwood intuitively in accordance with the optimum physical properties and in a sustainable way. A fuelwood shortage, however, was found to impact negatively on work and social practices and fuelwood was collected through destructive harvesting practices, such as the cutting of green branches, and without consideration for optimum timber properties, such as tree age and calorific value.